Zn2SnO4 ternary metal oxide for ultraviolet radiation filter application: a comparative study with TiO2 and ZnO - Kadhim Al-Attafi; Amar Al-Keisy; Muhammad A. Alsherbiny; Jung Ho Kim (Science and Technology of Advanced Materials, 2023)
ABSTRACTUltraviolet (UV) radiation causes serious health risks. Inorganic metal oxides, such as titanium dioxide (TiO2) and zinc oxide (ZnO), have long been recognized for their effectiveness as UV radiation filters/blockers in sunscreen formulations. TiO2 and ZnO as UV-blocking materials have some limitations and issues such as producing harmful radicals and toxicity, respectively. As a result, there is a growing need to develop efficient and safe UV-blocking materials to overcome these limitations associated with the conventional TiO2 and ZnO materials. Zinc stannate (Zn2SnO4), as a ternary metal oxide, is expected to be a promising candidate due to its optical properties and potential for UV-blocking capability. This study presents a comprehensive investigation into the development and characterization of Zn2SnO4 as a potential alternative UV filter to TiO2 and ZnO. The fundamental characteristics, including structural, optical, and photocatalytic characteristics, as well as cell viability, were investigated for two Zn2SnO4 morphologies: cubic aggregate Zn2SnO4 nanoparticles (ZTO CANP) and Zn2SnO4 nanoparticles (ZTO NP), which were compared with the performance of TiO2 nanoparticles (TiO2 NP) and ZnO nanoparticles (ZnO NP). Interestingly, in addition to their promising UVB and partial UVA blocking properties, ZTO CANP and ZTO NP were found to be relativity photocatalytically inactive materials, which means they produce less free radical species as in the case of TiO2 NP, and they cannot be considered as toxic materials as in the case of ZnO NP. To the best of our knowledge, this is the first direct comparison study examining the performance of Zn2SnO4 ternary metal oxide for its potential use as a UV filter. Further research and optimization need to be conducted on these materials, particularly on ZTO CANP as a promising alternative UV filter.